Assessing Non- Native EFL Electrical Engineering Students’ Argumentation Performance through Toulmin’s Model-based Argumentative Genre Essay - Marsaulina, Rumondang Miranda (Jurnal Ilmiah Wahana Pendidikan, 2024)
The purpose of this study is to evaluate applied comprehension of fresh year Electrical Engineering students, as non-native EFL adult learners at an IT institute in a remote area using, Toulmin’s model. The design and procedure of implementing this study with the subject of study encompassing 8 writing teams, sampled out of 16 writing teams formed by 47 Electrical Engineering students, was qualitative approach and summative content analysis. The main finding reveals students have remained to demonstrate less satisfying learning outcome when accomplishing argumentative genre essay task which is providing a compelling argumentation. Factors identified for such low-to-average quality despite rigid Toulmin’s model application for argumentation in their essay include the absence of thesis statement equivalent to the claim of an argumentative essay resulting in irrelevant reasons and insufficient evidence far from warranting it to the claim and lack of comprehension to compose a part anticipating critics’ rebuts. This study contributes to provide a comprehensive insight into students’ performance of developing argumentation through an academic essay after composing Toulmin’s model argumentative genre writing, expected to boost further research for teaching and learning methods helping students overcome their obstacles in building compelling arguments.